Host plant resistance to infestation of Fall armyworm, Spodoptera frugiperda (J. E. Smith), in tropical maize, (Zea mays L.), germplasm - Udah, O. (Obafemi Awolowo University, 2024)
The study evaluated early and extra-early maturing maize inbred lines to identify adaptive traits for resistance to Fall armyworm (FAW); determined the genetic control of resistance to FAW among selected early and extra early maturing maize inbred lines; identified the most critical stage(s) of different maize genotypes to FAW infestation; evaluated the effects of selected secondary metabolites on food preference of FAW; and determined the inhibitory efficacy of selected early maturing maize inbreds and hybrids against digestive enzymes of FAW. These were with a view to improving maize output and food security in Nigeria. A three-year study at Obafemi Awolowo University in Nigeria screened 1037 maize inbred lines for FAW damage. Early and extra-early maturing lines were divided into eleven groups based on maturity and endosperm color. Artificial infestation with FAW larvae was carried out two weeks after planting, with an average of four larvae per plant stand. Resistance was evaluated throughout the plants' growth stages using a rating scale. The study also included experiments on secondary metabolites and enzyme inhibition assays. Data from both resistant and susceptible lines were analyzed at the OAU Enzymology laboratory. Data obtained for each objective were subjected to analysis of variance and significant means were compared using least significant difference at p ≤ 0.05. Specifically, the adaptive traits were identified based on their significant relationships with the insect’s damage parameters using correlation and stepwise multiple regression analyses. The study identified 150 FAW resistant inbred lines as potential trait donors for breeding programmes. Nine adaptive traits were identified, with the number of days to anthesis and silking significantly correlated with FAW damage (p ≤ 0.05). The study revealed significant ((p ≤ 0.01) genetic variability among inbred lines, with both additive and non-additive gene actions influencing FAW damage. All tested maize hybrids contained flavonoids, triterpenes, and phenolics, while saponins were absent in all samples. The secondary metabolite profile of maize plant materials screened will be useful for selecting resistant germplasms, particularly for flavonoids. The genetic makeup of inbred lines and hybrids significantly influenced enzyme inhibition, with variability primarily due to genetic differences. Alpha amylase inhibition percentages in pro-vitamin A maize inbreds and hybrids revealed TZEIOR 192 as the most effective inbred line. TZEIOR 70, a FAW susceptible inbred parent, performed better than some potentially resistant lines, indicating multiple defense mechanisms may be responsible for resistance in the maize inbreds and hybrids studied. In conclusion, the study identified potential FAW resistant maize inbred lines. Male parents had additive gene action controlling FAW damage parameters, while pro-vitamin A maize inbred lines had non-additive gene action. Secondary metabolites played a crucial role in defense mechanisms against FAW, with flavonoids, triterpenes, and phenolics influencing FAW larvae's feeding preferences. Extracts from selected maize lines showed inhibitory activity against FAW digestive enzymes.